Rare Earth Metal-Based Intermetallics Formation in Al–Cu–Mg and Al–Si–Cu–Mg Alloys: A Metallographic Study - A. M. Samuel; E. M. Elgallad; M. G. Mahmoud; H. W. Doty; S. Valtierra; F. H. Samuel (Advances in Materials Science and Engineering, 2018)
This study was conducted on Al–Cu–Mg and Al–Si–Cu–Mg alloys containing either 5%La or 5%Ce. Two levels of Ti addition were examined, i.e., 0.05% and 0.15%. Thermal analysis was the only technique used to obtain castings, from which samples were then sectioned for metallographic examination. Based on the results obtained, the following points may be highlighted. Addition of a fairly large amount of RE metals (La or Ce) leads to the appearance of several peaks in the solidification curve between the precipitation of the primary α-Al phase and the (Al–Al2Cu) eutectic reaction. Although a significant drop in the eutectic temperature is caused by the addition of 5%La or Ce, the corresponding modification of the eutectic Si is marginal. Two main types of intermetallics were documented: a gray phase in the form of sludge with a fixed composition and a white phase in the shape of thin platelets. Due to the high affinity of RE to react with Si, Fe, and Cu, several compositions were obtained explaining the observed multiple peaks in the solidification curve. Judging by the morphology of the gray phase, it is assumed that this phase is precipitated in the liquid state and acts as a nucleation site for the white phase. Lanthanum and Ce can substitute each other.